Liability for Third-Party Harm When Harm-Inflicting Consumers Are Present Biased. (4th February 2020) - Friehe, Tim; Rößler, Christoph; Dong, Xiaoge
Abstract: This article analyzes the workings of liability when harm-inflicting consumers are present biased and both product safety and consumer care influence expected harm. We show that present bias introduces a rationale for shifting some losses onto the manufacturer, in stark contrast with the baseline scenario in which strict consumer liability induces socially optimal product safety and precaution levels. In addition, we establish that strict liability with contributory negligence may induce socially optimal product safety and precaution choices.